2015
DOI: 10.1210/en.2015-1785
|View full text |Cite
|
Sign up to set email alerts
|

Actions of Bisphenol A and Bisphenol S on the Reproductive Neuroendocrine System During Early Development in Zebrafish

Abstract: Bisphenol A (BPA) is a well-known environmental, endocrine-disrupting chemical, and bisphenol S (BPS) has been considered a safer alternative for BPA-free products. The present study aims to evaluate the impact of BPA and BPS on the reproductive neuroendocrine system during zebrafish embryonic and larval development and to explore potential mechanisms of action associated with estrogen receptor (ER), thyroid hormone receptor (THR), and enzyme aromatase (AROM) pathways. Environmentally relevant, low levels of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(84 citation statements)
references
References 68 publications
3
80
1
Order By: Relevance
“…Exposure to BPS (100 μg/L) for the same embryonic time period resulted in increased number of GnRH3 neurons and upregulated expression of kiss1 , gnrh3 , and esr1 . In contrast to the above study that indicated the neural effects of BPS were independent of ESR1 [99], the findings from this other study showed that antagonists to ESRs, THRs, and aromatase inhibitor blocked most of the gene expression changes induced by BPA or BPS (at the 100 μg/L exposure dose) [100]. Exposure of 4 or 7 days post-fertilization (dpf) larvae to BPS, BPF, or BPAF (1 μM concentration) activated the expression of aromatase B (cyp19a1b) in the hypothalamus of developing zebrafish, and competitive ligand binding assays revealed this effect was mediated through zFER [28].…”
Section: Neuroendocrine Disruption Due To Bisphenol S or Bisphenol F contrasting
confidence: 59%
See 3 more Smart Citations
“…Exposure to BPS (100 μg/L) for the same embryonic time period resulted in increased number of GnRH3 neurons and upregulated expression of kiss1 , gnrh3 , and esr1 . In contrast to the above study that indicated the neural effects of BPS were independent of ESR1 [99], the findings from this other study showed that antagonists to ESRs, THRs, and aromatase inhibitor blocked most of the gene expression changes induced by BPA or BPS (at the 100 μg/L exposure dose) [100]. Exposure of 4 or 7 days post-fertilization (dpf) larvae to BPS, BPF, or BPAF (1 μM concentration) activated the expression of aromatase B (cyp19a1b) in the hypothalamus of developing zebrafish, and competitive ligand binding assays revealed this effect was mediated through zFER [28].…”
Section: Neuroendocrine Disruption Due To Bisphenol S or Bisphenol F contrasting
confidence: 59%
“…Another study that compared the neuroendocrine changes induced by developmental exposure to BPA or BPS also found that both chemicals resulted in similar alterations [100]. Low levels of BPA exposure (0.1 to 1000 μg/L) from 2 hpf until either 25 or 120 hpf led to advanced hatching time, increased numbers of gonadotrophin releasing hormone 3 (GnRH3) neurons in the terminal nerve region and hypothalamus (at the 100 μg/L dose).…”
Section: Neuroendocrine Disruption Due To Bisphenol S or Bisphenol F mentioning
confidence: 96%
See 2 more Smart Citations
“…The study of Qiu and colleagues evaluated the impact of BPA and BPS on the reproductive neuroendocrine system during zebrafish embryonic development, and explored potential mechanisms of action associated with ER, thyroid hormone receptor, and enzyme aromatase pathways. All of these pathways were necessary to observe the full effects of BPS on the changes in gene expression in the reproductive neuroendocrine axis (Qiu et al 2016). These data were substantiated by a decrease in egg production and hatchability and an increasing number of embryo malformations (Ji et al 2013).…”
Section: Biological Effects Of Bpsmentioning
confidence: 98%